(untitled) (Journal of Nobel Medical College, 2025)
Background: Immunization and cold chain management are integral to public health. Though traditional medicine curriculum includes these topics, students often lack practical exposure. This study evaluates the impact of lecture combined with vaccination center visit on knowledge of immunization and cold chain management among these students. Materials and Methods: A longitudinal, quasi-experimental study was conducted on traditional medicine students visiting the tertiary care hospital in Kolkata from June to December 2024. The intervention includedtwo-hour lecture followed by two-hour vaccination center visit. Knowledge assessments were conducted pre-intervention, post-intervention, and after one-month using a 20-item e-questionnaire on Vaccination &Adverse Event Following Immunisation, Cold Chain and Biomedical Waste Management.Comparisons between pre-test, post-test, and post-1-month test scores were conducted using Friedman test. Results: Among the 80 participantscompleting the study, median scores across all domains improved significantly (Friedman test p <0.001). Vaccines &Adverse Event Following Immunisation scores increased from a median of 0 in the pre-test to 9 in the post-test, with a slight decline to 7.5 after 1-month. Cold Chain scores rose from 2 to 5 and remained stable (post-test vs post-1-month test p 0.386). Biomedical Waste Management scores improved from 1 to 4.5 in the post-test, decreasing marginally to 4 after one month. Total scores showed a remarkable rise from a median of 4 to 17, with slight decline to 15 after a month. Conclusion: Experiential learning combined with lectures enhances knowledge retention among traditional medicine students, highlighting the need for integration of practical training in the curriculum.